2011
DOI: 10.1016/j.csda.2010.05.030
|View full text |Cite
|
Sign up to set email alerts
|

Nonlinear methods for inverse statistical problems

Abstract: In the uncertainty treatment framework considered in this paper, the intrinsic variability of the inputs of a physical simulation model is modelled by a multivariate probability distribution. The objective is to identify this probability distribution -the dispersion of which is independent of the sample size since intrinsic variability is at stake -based on observation of some model outputs. Moreover, in order to limit to a reasonable level the number of (usually burdensome) physical model runs inside the inve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 12 publications
0
10
0
Order By: Relevance
“…Kriging is massively used in global optimization and uncertainty quantification [7] [8,9] [10] [11]. As pointed out in [12], often in practical applications, Kriging is mostly used in its basic configuration known as Ordinary Kriging, because of the lack of a priori knowledge about the main trends of the function of interest.…”
Section: Introductionmentioning
confidence: 99%
“…Kriging is massively used in global optimization and uncertainty quantification [7] [8,9] [10] [11]. As pointed out in [12], often in practical applications, Kriging is mostly used in its basic configuration known as Ordinary Kriging, because of the lack of a priori knowledge about the main trends of the function of interest.…”
Section: Introductionmentioning
confidence: 99%
“…Celeux et al (2010) considered a maximum likelihood estimation by expectation-conditional maximisation either (Liu & Rubin, 1994) based on an iterative linearisation of H: this algorithm should be avoided if the nonlinearities of H relative to x are significant; otherwise, it can be very efficient. Barbillon, Celeux, Grimaud, Lefebvre, and de Rocquigny (2011) proposed to couple a stochastic expectation maximisation algorithm (Celeux & Diebolt, 1988) with a kriging metamodelling of H to improve the robustness of the estimation.…”
Section: Introductionmentioning
confidence: 99%
“…A frequentist technique that is premised on the simulation of an explicitly marginalized likelihood is proposed in [32]. There are also attempts to compute approximate solutions based on variants of the expectation-maximization algorithm within a linearized Gaussian frame [33] or with the aid of Kriging surrogates [34]. A methodological review of this school of probabilistic inversion is found in [35].…”
Section: Introductionmentioning
confidence: 99%